2013
DOI: 10.6113/jpe.2013.13.6.939
|View full text |Cite
|
Sign up to set email alerts
|

Novel Switching Table for Direct Torque Controlled Permanent Magnet Synchronous Motors to Reduce Torque Ripple

Abstract: The Direct Torque Control (DTC) technique for Permanent Magnet Synchronous Motors (PMSM) is receiving increased attention due to its simplicity and robust dynamic response when compared with other control techniques. The classical switching table based DTC results in large flux and torque ripples in the motors. Several studies have been reported in the literature on classical DTC. However, there are only limited studies that actually discuss or evaluate the classical DTC. This paper proposes, novel switching t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…WITH RECENT SIMILAR METHODS After investigating the recent studies presented about the ripple reduction in DTC method, it is observed that the methods proposed in [9] and [37] have a good performance in both the steady-state and transient-state; hence, these two methods are selected to be compared with the predictive method proposed in this paper. In this section the comparison is done from the analytical point of view while in sections IV and V the comparison is done by using simulations and experimental tests.…”
Section: Analytical Comparison Of the Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…WITH RECENT SIMILAR METHODS After investigating the recent studies presented about the ripple reduction in DTC method, it is observed that the methods proposed in [9] and [37] have a good performance in both the steady-state and transient-state; hence, these two methods are selected to be compared with the predictive method proposed in this paper. In this section the comparison is done from the analytical point of view while in sections IV and V the comparison is done by using simulations and experimental tests.…”
Section: Analytical Comparison Of the Proposed Methodsmentioning
confidence: 99%
“…Based on (8), because the values of the βƒ—βƒ— βƒ— , βƒ—βƒ—βƒ—βƒ—βƒ— and βƒ—βƒ—βƒ—βƒ—βƒ— can be obtained in every control cycle, by proper control of the βƒ—βƒ—βƒ—βƒ— one can control the motor torque towards a desirable value. If it is assumed that: 1) duration of one control period is equal to , 2) a non-zero voltage vector ( βƒ—βƒ—βƒ—βƒ— ) is applied to the motor with a time duration of , and 3) a zero voltage vector is applied to the motor in the rest of the control period, then, based on (8), the result of these voltage vectors on the torque is calculated by (9) and (10), respectively: | βƒ—βƒ—βƒ—βƒ—βƒ— || βƒ—βƒ—βƒ—βƒ— | βƒ—βƒ—βƒ—βƒ—βƒ— βƒ—βƒ—βƒ—βƒ—βƒ—…”
Section: ) Discrete Time Representation Of the Motor Torquementioning
confidence: 99%
See 2 more Smart Citations
“…The first is the high torque and flux ripples, whereas the second is the variable switching frequency of the devices. Several methods have been proposed to overcome these problems by using modified DTC techniques [2]- [9].…”
Section: Introductionmentioning
confidence: 99%